IDENTIFICATION OF ELECTROMAGNETIC INTERFERENCE ON THE DC SIDE OFF-GRID PHOTOVOLTAIC INVERTER USING DC LINE IMPEDANCE STABILIZATION NETWORK - Yudhistira
Identification of electromagnetic interference in the form of conducted emission noise caused by the inverter on the Off-Grid photovoltaic (PV) system has been successfully carried out and the quality description of the inverter related to its compatibility with the electromagnetic environment could be obtained by comparing the results of conducted emission noise measurement by inverter with the limits that exist on the standard. DC Line Impedance Stabilization Network (DC-LISN) is used as a noise receiver from the inverter and forward it to the Spectrum Analyzer and EMI Receiver measuring devices and acts as noise absorber from the voltage source so that it does not interfere with the measurement results. CISPR 16-1-2:2014 Standard is used as a guide for the design of DC-LISN designs and as a determination of the requirements for the fulfillment of DC-LISN as a measurement device of conducted emission noise inverter. The DC-LISN characteristics are impedance and insertion loss at a frequency of 150 kHz – 30 MHz was evaluated using an analytic method in the form of a transfer function (Bode Plot) and verified against the LT-Spice software simulation method. The results of these two methods serve as a reference for validation of the measurement results of DC-LISN impedance and insertion loss. The tolerance limit allowed by the standard, i.e. the impedance value is still in the range of ± 20% of the impedance value required by the standard and the insertion loss value is still below the maximum limit (-40 dB) has been met by DC-LISN so that this device could use as a measurement tool for conducted emission noise from inverter. The setup of conducted emission noise measurements is based on the CISPR 25: 2016 standard. Three modes were applied to measure conducted noise emission inverters, namely noise floor, no load, and load variation modes. Loads such as LED lights with different power, chargers, solder, and electric fan were used to determine the noise generated by the inverter due to the addition of load on the AC side. Three inverter samples with different power capacities, namely 200 W, 300 W, and 700 W were measured by applying the three modes. In this research, samples of 200 W and 300 W inverters were identified as inverters that did not meet the electromagnetic compatibility conditions because they had several Quasi Peak (QP) and Average Peak (AVP) values that exceeded the QP and AVP limits on the IEC 62920: 2017 standard. On the other hand, a sample of 700 W is identified as an inverter that has met the electromagnetic compatibility iv requirements in the form of conducted emission due to the absence of QP and AVP values that are above the limits allowed by the standard.